Penentuan Server Kritis Dengan Menggunakan Fuzzy Mamdani Dan Fuzzy Sugeno Pada PT SAMUDERA INDONESIA TBK - suhaemi suhaemi; Moedjiono Moedjiono; Arriyadi Ade Sunarto (Komunitas Dosen Indonesia, 2019)
CRITICAL SERVER DETERMINATION USING FUZZY MAMDANI AND FUZZY SUGENO METHODS :CASE STUDY PT SAMUDERA INDONESIA TBKBy : Suhaemi (1611601392)PT Samudera Indonesia Tbk is a company engaged in the field of logistics. As a service company, prioritizes services especially in providing information services to the customer or client. However, in the common problems of the technology information system which is used in particular is happening is the server down. This is due to several factors could not be predicted. Plus the company is still dependent on the role of the IT personnel to wait for handling server down occurrences. The effort to know the level of critical server is one of the prevention or mitigation of interference that are at risk of fatal to the business processes of the company then needed a decision support system. In this study, the author compares the mamdani fuzzy logic method calculations with fuzzy sugeno method to measure the level of critical servers used PT Samudera Indonesia Tbk. This research resulted in a prototype that is built with MATLAB R2013a, can be used to calculate the critical level on the server. The prototype uses two methods of fuzzy mamdani and sugeno fuzzy. Accuracy of Mamdani fuzzy method has a 85,21% average. Of the two methods of calculation, the highest accuracy rating results will serve as a reference in determining a critical server.Keywords: SPK, Server, Fuzzy Mamdani, Fuzzy Sugeno, Matlab R2013a